DEMOKRASI SEBAGAI IMPLEMENTASI DARI NILAI-NILAI PANCASILA DALAM PERILAKU MUSYAWARAH - Salim, Fahri (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Indonesia is one of the countries that adheres to a democratic system in running the government. Democracy by its essence according to Abraham Lincoln is a government of the people, by the people, and for the people. In this case, democracy allows all parties without exception to be involved in the realm of government. Even though the people are involved in it, the government of the country does not always run smoothly. Those who are appointed as representatives of the people are not always trustworthy in carrying out government duties. If a government that is not trustworthy continues to run, it will certainly reduce democratic values. In this case the democracy stated in Article 1 paragraph 2 of the 1945 Constitution of the Republic of Indonesia is only a scratch on paper. A clean and just government is certainly the hope of every citizen. In realizing a clean and just government, supporting indicators are needed in it. Pancasila as the basis of the state and the nation's way of life has regulated the Indonesian democratic system. Through the fourth precept, Pancasila introduces the values ​​of deliberation in reaching consensus which are then applied as the basis or rules that must be followed for every citizen. Deliberation which is one of the implementations of democracy is considered to be the best way to unite differences of opinion. According to Rifa'i (2015), the word deliberation is taken from Arabic, namely syura which is then absorbed in Indonesian so that it means to negotiate and consult. Indonesia, which is known to have diversity in various aspects such as ethnicity, religion, race, and between groups, certainly cannot be separated from differences of opinion. Therefore, making every decision in every aspect of national life cannot be separated from deliberation.